Perceived marriage readiness: A cross-cultural exploration - Adira, Nesya; Rismarini, Nadya Anjani; Nurhayati, Siti Rohmah (Psychological Research and Intervention, 2024)
Marriage readiness is considered an important issue to be studied. The high rates of marital problems which impact social issues have been attributed to the lack of marriage readiness. Number of studies have tried to define and explain marriage readiness indices. However, there are various limitations due to how this concept is very much influenced by cultural factors, as is the case in Indonesia which is famous for its variety of cultures in every region. This study was conducted to make a comparison between perceived marriage readiness between Javanese people, as the representation of the largest population in Indonesia and regions outside Java as the comparison group. Data was collected using open-ended surveys with 207 participants coming from all over Indonesia. The results were analyzed using thematic coding which describes marriage readiness factors and personal perception of marriage readiness among Indonesians. Implications for this study are discussed, especially for evaluation and development of existing marital guidance programs in Indonesia.